A case‐control analysis of hyperhemolysis syndrome in adults and laboratory correlates of complement involvement. Issue 10 (11th July 2019) - Merrill, Samuel A.; Brodsky, Robert A.; Lanzkron, Sophie M.; Naik, Rakhi
Abstract : BACKGROUND: Hyperhemolysis syndrome (HS) is a poorly understood, severe hemolytic anemia provoked by transfusion. Both host and donor RBCs are destroyed in HS; thus, transfusion paradoxically worsens anemia. Risk factors and mechanism of HS are unknown. STUDY DESIGN AND METHODS: A retrospective case‐control analysis was performed on adults with HS. Patients with HS were matched 1:1 with matched, transfused controls, and HS risk factors were analyzed with multivariable logistic regression. HS samples were analyzed for complement deposition by flow cytometry, and an in vitro model of bystander hemolysis was developed. RESULTS: Forty‐one patients with 54 episodes of HS were identified in a 26‐year period from 1992 to 2018. Of the HS episodes, only 18.5% were associated with a new alloantibody, and such patients were more tolerant of additional transfusion in the acute episode (p = 0.005). Thirteen percent of episodes were fatal, and HS recurred in 52.6%. Alloimmunization (odds ratio [OR], 17.3), non‐B blood type (OR, 9.8), D antigen (OR, 9.1), and infection (OR, 5.5) were associated with HS on multivariable analysis. Hyperbilirubinemia was predictive of fatal HS (OR, 33.6). Increased complement was observed on RBCs during HS episodes, and the in vitro model of bystander hemolysis recapitulated complement decoration of sickled RBCs. CONCLUSIONS: HS is associated with significant morbidity, mortality, and recurrence. Risk factors such as known alloimmunization, blood group, and infection predispose to HS. Bystander complement activation may drive HS. These factors may help physicians refine risk‐benefit assessments for transfusion and guide further therapeutic development.